FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN ASI PADA IBU PASCA SALIN DI RSUD. DR PIRNGADI MEDAN - Vitrilina Hutabarat; Stefani Anastasia Sitepu; Novita Br Ginting Munthe (JURNAL KEBIDANAN KESTRA (JKK), 2019)
Breast milk is the liquid produced by the secretion of the mother's breast gland, which is given to babies from birth for 6 months, without adding or replacing with other foods or drinks. The Indonesian government targets exclusive breastfeeding coverage of 80%. The results of the 2010 Riskesdas in North Sumatra only reached 20.2%. From year to year, it declined, especially in Medan.This study aims to determine the factors associated with breastfeeding in postpartum mothers at the RSUD. Dr. Pirngadi Medan in 2015.The study design used was cross sectional in the primary data consisting of 48 respondents. The study was conducted on March 28-April 28, 2015 using a questionnaire filled out by the respondents themselves. Analysis of the data used is chi square. The results showed that most of the middle age were 56.3%, secondary education was 64.6%, working IRT as much as 100%, delivery by sectio caesarea as much as 70.8%, knowledgeable as much as 79.2%, sources of information from officers health as much as 62.5%, and those who received support as much as 83.3%. Proportion of breastfeeding to postpartum mothers at Dr. Pirngadi Medan is 83.3%, has more fulfilled the national target (80%). Factors related to breastfeeding in this study were knowledge (predisposing factors), sources of information (enabling factors) and husband / family support (reinforcing factors). From the results of this study it can be concluded that good knowledge (predisposing factors), sources of information from health workers (enabling factors) and husband / family support (reinforcing factors) can influence breastfeeding in postpartum mothers.